Societal Wellbeing Disclosure, Corporate Governance, and‎Financial Reporting Quality: Evidence from Malaysia - Zaim , Nur Izzah Nasuha Mohd; Lode , Nor Asma; Ismail , Wan Adibah Wan (International Journal of Accounting and Economics Studies, 2025)
This study examines the relationship between societal well-being disclosure, governance mechanisms, and financial reporting quality (FRQ) ‎among Malaysian listed firms. Using 500 firm-year observations from 2018 to 2022, FRQ is measured using a modified Dechow and Dichev’s ‎accrual quality model. Regression analysis shows that female board representation is the only governance variable significantly associated with ‎improved FRQ. Other governance structures, including board size, independence, audit committee characteristics, leadership separation, and ‎meeting frequency, are not significant. Societal well-being disclosure also does not significantly influence FRQ, suggesting that sustainability ‎reporting remains largely symbolic in Malaysia. These findings extend agency and signaling theory by demonstrating that gender diversity ‎strengthened monitoring and reporting integrity, while also highlighting a gap in legitimacy and stakeholder theory, where societal well-being has ‎yet to influence financial reporting. Practically, the results imply that regulators should strengthen gender diversity initiatives and improve ‎substantive governance practices beyond structural compliance‎.